Evaluating the Influence of Students' Sense of Community and Self-Efficacy on Higher-Order Thinking Skills in Blended Learning Environments - Annisa Prasetyo Heni; Wayan Suana; Ni Made Anggi Arlina Putri (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2024)
This study aimed to determine the effect of students' sense of community and self-efficacy on their higher-order thinking skills (HOTS). The samples were students from class X MIPA 1 and X MIPA 2, totaling 66 science students at SMAN 1 Terbanggi Besar. The research design used was a post-test only design. Based on research using a single linear regression test, there was no effect of sense of communityon HOTS, with a correlation value of 0.184 and a coefficient of determination of 0.034, indicating that sense of communitycontributed only 3.4% to HOTS. Similarly, there was no effect of self-efficacy on HOTS, with a correlation value of 0.148 and a coefficient of determination of 0.022, indicating that self-efficacy contributed only 2.2% to HOTS. A multiple regression test also showed no effect of sense of communityand self-efficacy on HOTS, with a correlation value of 0.173 and a coefficient of determination of 0.030, indicating that sense of communityand self-efficacy together contributed only 3.0% to HOTS. It can be concluded that there is no significant effect of sense of community and self-efficacy on HOTS when using WhatsApp-assisted blended learning.